FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI IMPLAN PADA WANITA USIA SUBUR SAAT PANDEMI COVID-19 DI PUSKESMAS KELURAHAN MENTENG ATAS TAHUN 2022 - Syifa Fauziyah (2022)
The Covid-19 pandemic has affected the limited implant contraceptive services, resulting in a decline in the acceptors. Based on data from BKKBN, active implant contraceptive acceptors in Indonesia decreased by 0,55% from 2020 to 2021. Implant contraceptive acceptors in DKI Jakarta also decreased, one of the locations in South Jakarta which also decreased in implants contraceptive acceptors is Menteng Atas Village that declined by 0,8% after the pandemic. This study was conducted to determine the factors related to the use of implant contraceptives in women at reproductive age during the Covid-19 pandemic at the Menteng Atas Community Health Center and was carried out in April−June 2022. The research design in this study was Cross-Sectional. The sample selected by simple random sampling with a total of 110 respondents. The factors that have a relationship with the use of implant contraceptives are knowledge, attitudes, husband's support, and role models. The most dominant factor with the use of implant contraceptives is husband's support with POR= 20,585 (95% CI: 3,938-107,604). It is recommended to increase in communication, information, and education activities in the form of counseling and socialization of family planning so that it can increase the knowledge and awareness of women at reproductive age in using implant contraception.